Analisis Sonopattern Kandung Empedu Puasa 6 Jam dengan Puasa 8 Jam - Syahputra Wibowo (Poltekkes Kemenkes Semarang, 2026)
Background:Gallbladder ultrasonography is highly influenced by fasting status. Accordingly, numerous studies have demonstrated that adequate fasting plays a crucial role in optimizing ultrasound image quality and visualization. Some radiology centers require patients to fast for 6 to 8 hours prior to an ultrasound examination. Nevertheless, excessively prolonged fasting may lead to patient discomfort, increase the risk of hypoglycaemia in diabetic patients, and disrupt workflow efficiency within hospital radiology services. The aim of this study is to obtain high-quality ultrasound images by comparing these two fasting strategies. Methods: This research employed a qualitative method with an analytical observational approach. The research was conducted at Health Polytechnic of Ministry of Health Jakarta II over a two-month period, from December 2025 to January 2026. A total of 12 samples were purposely selected, comprising examinations performed after 6-hour fasting and 8-hour fasting. Results: Gallbladder ultrasonography after 6-hour fasting demonstrated generally adequate sonographic patterns, with normal wall thickness and no evidence of gallstones or sludge, although some cases showed less optimal distension. In contrast, 8-hour fasting provided greater gallbladder distension and clearer lumen visualization, facilitating more optimal structural assessment. Overall, both fasting durations produced diagnostically acceptable images, with 8-hour fasting yielding superior visualization, while 6-hour fasting remained sufficiently reliable and more efficient. Conclusions: the findings of this research indicate that a 6-hour fasting duration is both evidently more effective and efficient for gallbladder ultrasonography. This duration was shown to produce sonographic patterns comparable to those obtained after 8 hours of fasting, without compromising diagnostic quality. Moreover, 6-hour fasting period offers additional advantages in terms of the patient comfort and improved efficiency of radiology services.